2014
DOI: 10.4102/jef.v7i1.128
|View full text |Cite
|
Sign up to set email alerts
|

Identifying accessible export opportunities for South Africa in South America

Abstract: Despite the surging demand for imports in South America in recent years, South Africa’s exports to the region have shown relatively low growth. A contributing factor is the prevalence of trade barriers between South Africa and various South American countries. The aim of this study is, firstly, to measure the trade barriers to South Africa’s exports to South America and, secondly, to identify high-potential export opportunities in the form of product-country combinations that can best surmount such barriers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The tariffs and non-tariff measures in Brazil, Colombia, Uruguay, and Venezuela, time to import (almost double that of competitors on average), cost to import (on average 26% higher than other destinations), and poor English proficiency in business circles in most South American countries are the most common barriers that South African exporters face in South America [ 40 ]. The study carried out by Bazani, Pereira [ 41 ] revealed that in comparison to other countries, Brazil has a middling logistics performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The tariffs and non-tariff measures in Brazil, Colombia, Uruguay, and Venezuela, time to import (almost double that of competitors on average), cost to import (on average 26% higher than other destinations), and poor English proficiency in business circles in most South American countries are the most common barriers that South African exporters face in South America [ 40 ]. The study carried out by Bazani, Pereira [ 41 ] revealed that in comparison to other countries, Brazil has a middling logistics performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study uses the 2010 TRADE-DSM results in order to correspond with the 2010 SARS export data used to calculate the RCA scores for Mpumalanga. The TRADE-DSM involves a sequential filtering process with four filters that identify products and markets with the most REOs for export success (Jacobs, Viviers & Steenkamp 2014). The TRADE-DSM can therefore be used to justify the allocation of public resources to promote products with the highest export potential ).…”
Section: Factors Influencing the Decision For Firms To Exportmentioning
confidence: 99%